The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/mp.12581
|View full text |Cite
|
Sign up to set email alerts
|

Neutron damage induced in cardiovascular implantable electronic devices from a clinical 18 MV photon beam: A Monte Carlo study

Abstract: Clinically, increasing the depth or the distance from the central axis to the CIED will reduce the probability of damage from neutrons. Care must be taken when treating large fields as the overall probability of damage increase as does the distance the higher probability of damage extends beyond the field edge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Since neutron dose reflects both neutron spectrum and energy dependence of the nuclear reaction cross‐section, however, it shows linearity with the number of malfunctions. Such discussion has already been partly reported …”
Section: Methodsmentioning
confidence: 67%
See 1 more Smart Citation
“…Since neutron dose reflects both neutron spectrum and energy dependence of the nuclear reaction cross‐section, however, it shows linearity with the number of malfunctions. Such discussion has already been partly reported …”
Section: Methodsmentioning
confidence: 67%
“…In spite of such numerous studies, however, a quantitative understanding of malfunction has not been reached. Although only one study reported the damage to CIEDs by neutrons numerically, it was just a relative value based on a Monte Carlo calculation.…”
Section: Introductionmentioning
confidence: 99%